(untitled) (Global Journal of Management and Business Research, 2020)
In this competitive world highly skilled manpower is considered to play key role in developing a nation. On the other hand, highly educated people are blamed for recent business and financial scandals. Moreover, studies established that pupils who deceive in their student life are found to be engaged in immoral workplace conduct. The Student today is the future leader of the country. Hence, the combination of quality with morality is emphasized in the universities of in many developed counties like the USA, China, and moral education is being imparted at all stages of academic organizations and training centers from kindergarten to national academia. Therefore, the goal of the research is to explore the origins of the unethical behavior of University students of Bangladesh and recommend the means to improve the situation.